2009
DOI: 10.1007/s10342-009-0288-0
|View full text |Cite
|
Sign up to set email alerts
|

Propagating the errors of initial forest variables through stand- and tree-level growth simulators

Abstract: Developments in the field of remote sensing have led to various cost-efficient forest inventory methods at different levels of detail. Remote-sensing techniques such as airborne laser scanning (ALS) and digital photogrammetry are becoming feasible alternatives for providing data for forest planning. Forest-planning systems are used to determine the future harvests and silvicultural operations. Input data errors affect the forest growth projections and these effects are dependent on the magnitude of the error. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The effects of the errors in the ITD were analyzed with Monte Carlo (MC) simulations (e.g., [30][31][32][33][34]). With the MC method the calculation procedure is run dozens or hundreds of times, the results of which are used to determine the final predicted value error statistics.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…The effects of the errors in the ITD were analyzed with Monte Carlo (MC) simulations (e.g., [30][31][32][33][34]). With the MC method the calculation procedure is run dozens or hundreds of times, the results of which are used to determine the final predicted value error statistics.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…The relative importance of the three sources of uncertainty in forest NPV computations was determined by simulating each stand within each forest property repeatedly with the MC method (e.g., [25,26,29,39]). In MC methodology, confidence estimates are obtained by generating an error term from the model's error distribution for each output estimate.…”
Section: Simulation Of the Sources Of Uncertaintymentioning
confidence: 99%
“…These studies have mainly focused on the influence of various uncertainty components in growth model functioning. However, Mäkinen et al [25] and Mäkinen [30] showed that instead of analyzing individual models, the model chains implemented by the simulators should be scrutinized as a whole.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations